Expression of insulin-like growth factor I by activated hepatic stellate cells reduces fibrogenesis and enhances regeneration after liver injury. Issue 1 (10th December 2004) - Sanz, S; Pucilowska, J B; Liu, S; Rodríguez-Ortigosa, C M; Lund, P K; Brenner, D A; Fuller, C R; Simmons, J G; Pardo, A; Martínez-Chantar, M-L; Fagin, J A; Prieto, J
Abstract : Background/Aim: Hepatic stellate cells (HSCs) express α-smooth muscle actin (αSMA) and acquire a profibrogenic phenotype upon activation by noxious stimuli. Insulin-like growth I (IGF-I) has been shown to stimulate HSCs proliferation in vitro, but it has been reported to reduce liver damage and fibrogenesis when given to cirrhotic rats. Methods: The authors used transgenic mice (SMP8-IGF-I) expressing IGF-I under control of αSMA promoter to study the influence of IGF-I synthesised by activated HSCs on the recovery from liver injury. Results: The transgene was expressed by HSCs from SMP8-IGF-I mice upon activation in culture and in the livers of these animals after CCl4 challenge. Twenty four hours after administration of CCl4 both transgenic and wild type mice showed similar extensive necrosis and increased levels of serum transaminases. However at 72 hours SMP8-IGF-I mice exhibited lower serum transaminases, reduced hepatic expression of αSMA, and improved liver morphology compared with wild type littermates. Remarkably, at this time all eight CCl4 treated wild type mice manifested histological signs of liver necrosis that was severe in six of them, while six out of eight transgenic animals had virtually no necrosis. In SMP8-IGF-I mice robust DNA synthesis occurred earlier than in wild type animals and this was associated with enhanced production of HGF and lower TGFβ1 mRNA expression in the SMP8-IGF-I group. Moreover, Colα1(I) mRNA abundance at 72 hours was reduced in SMP8-IGF-I mice compared with wild type controls. Conclusions: Targeted overexpression of IGF-I by activated HSCs restricts their activation, attenuates fibrogenesis, and accelarates liver regeneration. These effects appear to be mediated in part by upregulation of HGF and downregulation of TGFβ1. The data indicate that IGF-I can modulate the cytokine response to liver injury facilitating regeneration and reducing fibrosis.